Myths and Failure of Exclusive Breastfeeding: Study in Buaran Community Health Center Pekalongan Regency Central Java - Isytiaroh Isytiaroh (IJNP (Indonesian Journal of Nursing Practices), 2018)
AbstractBackground: Failure of exclusive breastfeeding is still high in Pekalongan regency, Central Java Indonesia. The one of reasondue to the existing myth about breast milk and breastfeeding activity in society culture.Objective: This study aimed to determine the relationship between myth about breastfeeding and failure of exclusive breastfeeding.Method: This cross-sectional study design conducted among 151 mothers with infant 6-12 month age which selected by cluster sampling, in Buaran Community Health Center in Pekalongan Regency Central Java Indonesia, from January to May 2017. An instrument used was a questionnaire developed by the reseacher. Result: The results showed 70.1% participants failed exclusive breastfeeding, 56.9% of them believed negative myths about exclusive breastfeeding by p = 0.001 (95% CI: 1,757-8,057). The characteristic of participants was in reproductive age (81,5%), multiparous (71,5%), unemployed (70,9%), and from extended family (66,9%). Most of the participants had a vaginal delivery (86,8%).  There was asignificant relationship between myths about breastfeeding and failure of exclusive breastfeeding.  Breastfeeding education should deliver in community-based, in terms of growing breastfeeding culture, in Indonesian society.